Calcium Nutrition in Coffee and Its Influence on Growth, Stress Tolerance, Cations Uptake, and Productivity - Ramírez-Builes, Victor Hugo; Küsters, Jürgen; de Souza, Thais Regina; Simmes, Christine (Frontiers in Agronomy, 2020)
Calcium (Ca2+) is an important macronutrient in coffee and is involved in several physiological processes that influence crop growth, development, productivity, and stress response. This paper presents results from five experiments conducted on coffee under greenhouse and field conditions for over five years (2014–2018). The main objective of this study was to evaluate the influence of Ca+2 application on coffee growth, development, abiotic stress response, cation uptake, leaf cell structure, and productivity. The results show that Ca+2 directly influences the growth and development of plants and has a strong effect on root growth. Drought stress and low Ca+2 rates of 8 mg.L-1 showed no differences in photosynthetic rates (PN) and biomass accumulation; high Ca+2 rates between 75 to 150 mg.L-1 increased PN and biomass accumulation in plants under drought stress, with a positive correlation between Ca+2 content in the leaves and PN with and without drought stress. High air temperature (>30°C) reduced PN rates, and the treatment with proper Ca+2 application showed better PN compared to the treatments with low Ca+2. Ca+2 application showed a synergistic effect with potassium (K+) uptake and no influence on the magnesium (Mg+2) uptake but a reduction in the leaf concentration with the increase in Ca+2 application. Additionally, coffee plants with proper Ca+2 application showed thicker leaves, denser epidermis, and larger, more compact, and better-structured palisade parenchyma compared with the plants treated with Ca+2 at lower rates. After five years, the mean coffee yield showed a polynomial response with respect to the doses of Ca+2 applied, with optimum rate of 120 kg CaO ha-1year-1 and a peak of Ca+2 uptake by the coffee cherries during 110 to 220 days after flowering.